Rose Bengal staining - diagnostic aid for potentially malignant and malignant disorders: A pilot study - Nitasha Mittal; Sangeeta Palaskar; Madhu Shankari (Wolters Kluwer Medknow Publications, 2012)
Background: The word "Cancer" itself is sufficient to cause a fear in the minds of people. Early detection of oral potentially malignant and malignant disorders is still a diagnostic challenge for most of the clinicians. In the present study, we have evaluated the efficacy of Rose Bengal staining in the detection of oral premalignant and malignant lesions. Aim: The aim of the study was to evaluate the efficacy of the Rose Bengal staining for the identification of dysplastic areas clinically, and then correlating the findings with the histological grading of dysplasia. Methods and Materials: A total of 20 patients were selected for the study. Patients had been evaluated clinically and histopathologically along with the grading of dysplasia, and Rose Bengal stain was painted over the lesional mucosa with the patient's consent. Incisional biopsies were taken from the stained area of the Rose Bengal dye, and studied histopathologically. Grading of dysplasia and intensity of the Rose Bengal staining were found to be correlated. Chi square test was performed and a statistical significance of P<0.001 was observed. Statistical significance was defined as P<0.001. Results and Conclusion: Grading of dysplasia and the intensity of Rose Bengal staining were directly proportional to each other according to this study. P value was found to be significant. Thus Rose Bengal stain can be used as a diagnostic aid in the detection of oral potentially malignant and malignant disorders.